2014
DOI: 10.11002/kjfp.2014.21.3.404
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of extracts from soybean and small black bean

Abstract: This study was carries out to analyzed the antioxidant activities of extracts extrated from soybean and small black bean for the development of functional materials. Yields of hot-water and ethanol extracts were higher in the soybean than small black bea, and yields of hot-water extracts were higher than ethanol extracts. Total phenol contents were 26.22 mg/g in the ethanol extracts from small black bean, and were higher than those in the soybean extracts. Total flavonoid contents were 30.52 mg/g of hot-water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The TPC of the CW from the studied legumes showed higher values for BSB and SBB than those of the CW from YSB and CH. This is in agreement with a previous study, which found a higher TPC in the hot water extracts of SBB than in that of YSB [28]. Furthermore, a study performed by Xu and Chang [29] determined that the decrease in the content of phenolic compounds after cooking was greater for black soybeans than for yellow soybeans, suggesting that the concentration of TPC in the CW of the dark variants was higher than that in the CW of yellow beans.…”
Section: Total Polyphenol Content (Tpc) and Phsupporting
confidence: 92%
“…The TPC of the CW from the studied legumes showed higher values for BSB and SBB than those of the CW from YSB and CH. This is in agreement with a previous study, which found a higher TPC in the hot water extracts of SBB than in that of YSB [28]. Furthermore, a study performed by Xu and Chang [29] determined that the decrease in the content of phenolic compounds after cooking was greater for black soybeans than for yellow soybeans, suggesting that the concentration of TPC in the CW of the dark variants was higher than that in the CW of yellow beans.…”
Section: Total Polyphenol Content (Tpc) and Phsupporting
confidence: 92%
“…According to Hong et al . ( 24 ), the total polyphenol and flavonoid contents of black soybean ( R. nulubilis ) water extract were 23.0 and 30.5 mg/g, respectively. Therefore, RNEE and RVEE have a higher antioxidant activity than R. nulubilis water extract.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with these studies, we observed that the DPPH scavenging activity, TPC, antioxidant peptides, and aglycone form of isoflavones (daidzein, glycitein, and genistein) were significantly increased in GR after fermentation with LAB [ 33 ]. The increased antioxidant activity of GR-SC65 could be attributed to the increased content of isoflavone aglycones (daidzein, glycitein, and genistein) [ 34 ] and four soy β-conglycinin peptides (INAENNQRNF, ISSEDKPFN, LAFPGSAQAVEK, and LAFPGSAKDIEN) [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%